Encountering development : the making and unmaking of the Third W orld - Escobar, Arturo, 1952- (Princeton, N.J. : Princeton University Press, 1995)
"Evaluates development enterprise and development discourse from a c ritical theory perspective. This view of development policies and contr ol mechanisms employs Colombian case studies of the Programa de Desarro llo Rural Integrado and of the local application of the discourse of wo men in development"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references (p. [249]-274) and index.
Keywords: Economic development; Economic history -- 1945-; Developing countries -- Economic conditions; Developing countries -- Social conditions